Ekspresi Sastra dan Visual: Analisis Konten Kanal Youtube Rekam Nusantara Sebagai Media Kampanye Lingkungan - Arni Yuniar Prastika; Muhitotun Nadhifah; Rafika Dini; Nuril Ahmad (Pusat riset dan Inovasi Nasional, 2025)
The use of digital media as a medium to communicate social messages is increasingly widespread, including in environmental conservation campaigns. One of the platforms used is YouTube, which allows messages to be delivered through a visual and narrative approach. However, not all content produced is able to present emotional impacts and environmental awareness effectively. The strategy for delivering messages is an important factor, especially through literary and visual expressions that can build emotional closeness with the audience. The Rekam Nusantara YouTube channel is an interesting example to study because it combines literary and visual elements in conveying the message of an environmental cleanliness campaign. This study aims to analyze the forms of literary and visual expressions used in the channel and how effective they are in building audience awareness. This study uses a qualitative approach with a descriptive method, which systematically describes the characteristics of the content based on the data analyzed. Data were obtained through literature studies and analysis of video content published by the Rekam Nusantara channel. The results of the study show that this channel utilizes literary elements in the form of poetic narratives and a cinematic visual approach to move the emotions of the audience. However, the effectiveness of the campaign can still be improved by adjusting the theme to the local context and a more specific audience profile. These findings underscore the importance of a relevant and touching narrative-based content strategy to optimize the role of digital media in social and environmental campai.